Assessment of the coronavirus pandemic (COVID-19) impact on supply chain and SME manufacturing firms’ performance in Malaysia - Abdul Hamid, Abu Bakar bin; Ismail, Siti Zaleha; Uzir, Md Uzir Hossain (International Journal of Supply Chain Management, 2021)
As the backbone of the economy, SMEs contribute to employment and GDP of the country. The recent coronavirus pandemic outbreak has heavily affected every business but has particularly hit SMEs badly. Due to limited empirical evidence of the impact of COVID-19 on the supply chain capability and the performance of SME manufacturing firms across Malaysia, this project aims to investigate how the coronavirus pandemic outbreak affects supply chain and SMEs’ manufacturing performance and propose a framework for overcoming the crisis. This research focuses on SME manufacturing firms located in Selangor and Kuala Lumpur (Bangi, Shah Alam, and Ulu Kelang). A total of 17 SMEs manufacturing owner-managers (eight sub-sectors) were interviewed based on an open-ended questionnaire. The thematic analysis was conducted for coding, categorising and developing theme. The findings showed that they have between four and 26 years’ experience, three to 200 employees, and MYR 100k to 500m yearly income. The COVID-19 has impacted the electrical and electronics sector (76%) the worst, followed by metal fabrication (64%), automotive (63%), oil and gas (61%), furniture (54%), food and beverage (52%), paper printing (51%) sectors and the least impacted being textiles (43%). The thematic analysis reveal that two important themes were identified in supply chain performance pre, during and post pandemic: business sustainable strategy and government policy and support. Total 15 sub-themes were categorised for two main theme. This finding will help managers understand and develop the resilient strategies, and help government’s policy makers to better cope with the rapid and unexpected coronavirus pandemic situation that severely affect on-going business operations and performance.